A CASE REPORT ON ISCHEMIC HEPATITIS –SHOCK LIVER - A.J. MANJULA DEVI; B. SHANTHI; J. RATHI ROOPAVATHY (International Journal of Pharma and Bio Sciences, 2013)
Ischemic hepatitis or shock liver is defined as an extensive hepatocellular necrosis associated with a decrease in hepatic perfusion caused by inadequate blood or oxygen supply. Ischemic hepatitis refers to diffuse hepatic injury secondary to acute hypoperfusion. Herewith we report 19 years old male with a fracture shaft of Right femur following road traffic accident, corrected by open reduction & internal fixation. Intraoperatively patient developed hypotension and then post-operative wound infection leading to ischemic hepatitis.